Egypt - Setting Up a Postal Policy Unit within the Ministry of Communication and Information Technology - World Bank (Washington, DC, 2013)
This note proposes an organization chart, job descriptions, and budget needs; and singles out the short-term priority issues, such as tariff policy, universal service definition and funding mechanism, state of the competition, authorizations and licenses, and enabling legislation. While addressing these issues is a priority, it is also recommended that the Postal Policy Unit build a structured dialogue with the sector stakeholders in the Government of Egypt (GoE), Egyptian National Post Office (ENPO), unions, private sector operators, and customers (institutional, corporate, and private customers) at the national level, and the Universal Postal Union (UPU) and World Trade Organization (WTO) at the international level.